Assessments of molar volume of the binary C14 Laves phase. (September 2015) - Zhao, Jing-Yong; Liu, Wei; Lu, Xiao-Gang
Abstract: The molar volume of the C14 Laves phase has been evaluated at room temperature and atmospheric pressure for binary systems involving 31 elemental metals (i.e. Al, Ba, Be, Co, Cr, Fe, Hf, Lu, Mg, Mn, Mo, Na, Nb, Nd, Os, Pr, Re, Ru, Sc, Sm, Sr, Ta, Tb, Ti, Tm, V, W, Y, Yb, Zn and Zr) based on experimental data from the literature by means of the CALPHAD approach. The molar volume model adopted in the present work expresses the molar volume of a non-stoichiometric C14 Laves phase as a linear average of volumes of the constituting elements in the hypothetic C14 Laves structure. Model parameters have been obtained and yield reasonable descriptions of most experimental data. As a further comparison, the molar volume of the C14 Laves phase obtained by the first-principles calculations was compared with the assessment results which illustrates a reasonable consistency.